2017
DOI: 10.1149/2.1011713jes
|View full text |Cite
|
Sign up to set email alerts
|

Local Electrochemistry and In Situ Microscopy of Pitting at Sensitized Grain Boundary of Type 304 Stainless Steel in NaCl Solution

Abstract: To elucidate the pit initiation behavior of sensitized stainless steels, the anodic polarization of a single grain boundary was examined in 0.1 M NaCl (pH 5.4) at 298 K using a micro-electrochemical system. For Type 304 heat-treated at 923 K for 2 h, no pitting was initiated on a small area (ca. 100 μm × 100 μm) with a sensitized grain boundary without MnS inclusions. However, stable pitting was observed on the electrode area that was larger than ca. 200 μm × 200 μm. In situ microscopy revealed that the first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 30 publications
(46 reference statements)
1
19
0
1
Order By: Relevance
“…This can also be explained by depletion in chromium of the grain boundary areas at a higher heat input. In accordance with the observations presented, [57] it can be assumed that, with a heat input increase, the chromium-rich phases precipitate on the boundaries of MnS inclusions. As a result, there is a significant depletion in chromium in the regions close to MnS inclusions, which facilitates the formation of pits.…”
Section: Results Of the Pitting Corrosion Testingsupporting
confidence: 84%
See 2 more Smart Citations
“…This can also be explained by depletion in chromium of the grain boundary areas at a higher heat input. In accordance with the observations presented, [57] it can be assumed that, with a heat input increase, the chromium-rich phases precipitate on the boundaries of MnS inclusions. As a result, there is a significant depletion in chromium in the regions close to MnS inclusions, which facilitates the formation of pits.…”
Section: Results Of the Pitting Corrosion Testingsupporting
confidence: 84%
“…It has been shown that the Cr/Fe ratio is lower in this region than in the austenitic matrix; therefore, the formation of pits is easier. On the other hand, the co‐existence of MnS inclusions and chromium‐depleted zones at the grain boundaries is considered to be the critical factor in the pit initiation of sensitized AISI 304 stainless steels …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of these zones is responsible for susceptibility to intergranular corrosion of these steels . Pits are almost exclusively formed close to MnS inclusions, and in particular near MnS inclusions that intercept chromium‐depleted narrow zones near grain boundaries . It is possible that, in naturally aged AA2024 alloy, pit formation is facilitated near cathodic particles crossed by copper depleted zones near grain boundaries.…”
Section: Resultsmentioning
confidence: 99%
“…[55] Pits are almost exclusively formed close to MnS inclusions, and in particular near MnS inclusions that intercept chromium-depleted narrow zones near grain boundaries. [56] It is possible that, in naturally aged AA2024 alloy, pit formation is facilitated near cathodic particles crossed by copper depleted zones near grain boundaries. Pit formation in these zones can be the cause of insufficiently higher resistance to pit formation of this temper.…”
Section: Corrosion Characteristics Of Thementioning
confidence: 99%